2016
DOI: 10.1371/journal.pone.0158731
|View full text |Cite
|
Sign up to set email alerts
|

Author Disambiguation in PubMed: Evidence on the Precision and Recall of Author-ity among NIH-Funded Scientists

Abstract: We examined the usefulness (precision) and completeness (recall) of the Author-ity author disambiguation for PubMed articles by associating articles with scientists funded by the National Institutes of Health (NIH). In doing so, we exploited established unique identifiers—Principal Investigator (PI) IDs—that the NIH assigns to funded scientists. Analyzing a set of 36,987 NIH scientists who received their first R01 grant between 1985 and 2009, we identified 355,921 articles appearing in PubMed that would allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 18 publications
0
47
0
Order By: Relevance
“…We did not use any methods for author name disambiguation for researchers indexed under the same “LastName”, “ForeName” and “Initials”. [13, 14] We set N s to be equal to the number of publications for which we identified at least one author.…”
Section: Methodsmentioning
confidence: 99%
“…We did not use any methods for author name disambiguation for researchers indexed under the same “LastName”, “ForeName” and “Initials”. [13, 14] We set N s to be equal to the number of publications for which we identified at least one author.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, this study demonstrated that from the ORCIDs-linked labeled data, we can create stratified samples of names that are susceptible to specific disambiguation errors, merging or splitting, and thereby can help us better measure the DBLP's disambiguation performance. It is, however, unclear how well author records in ORCIDs can represent the population of authors in DBLP (Lerchenmueller and Sorenson, 2016). Moreover, the accuracy of ORCIDs records has not yet been properly evaluated.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…To build the publication histories of F32 recipients we need to ensure that two scientists with the same name on two different papers actually represent the same individual. Prior research documents that Author-ity disambiguates scientists with over 99% accuracy, across different levels of scientists' productivity, ethnicity, and name prevalence, for articles listed in PubMed (Lerchenmueller and Sorenson, 2016). We make use of this core data feature to not only assemble the publication histories of the F32 recipients, but also to identify the likely mentors of the F32 recipients as well as the research network of these mentors.…”
Section: Methodsmentioning
confidence: 99%